Lightship [book with audioplayer] - Floca, Brian ([Library Ideas, LLC], 2024)
You may never have heard of a lightship. Once, lightships anchored on waters across America, on the oceans and in the Great Lakes, floating where lighthouses could not be built. Smaller than most ships, but more steadfast, too, they held their spots, through calm and storm, to guide sailors toward safe waters. In these pages one lightship and her crew (and cat) again hold their place. The crew goes again from bow to stern, from keel to mast, to run their engines, shine their lights, and sound their horns. They run the small ship that guides the large ships. They are the crew (and cat) that work to make the ocean safe, that hold their place, so other ships can sail. Come aboard!